Planning under Uncertainty for Coordinating Infrastructural Maintenance - Scharpff, Joris; Spaan, Matthijs; Volker, Leentje; De Weerdt, Mathijs (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
We address efficient planning of maintenance activities in infrastructural networks, inspired by the real-world problem of servicing a highway network. A road authority is responsible for the quality, throughput and maintenance costs of the network, while the actual maintenance is performed by autonomous, third-party contractors. From a (multi-agent) planning and scheduling perspective, many interesting challenges can be identified. First, planned maintenance activities might have an uncertain duration due to unexpected delays. Second, since maintenance activities influence the traffic flow in the network, careful coordination of the planned activities is required in order to minimise their impact on the network throughput. Third, as we are dealing with selfish agents in a private-values setting, the road authority faces an incentive-design problem to truthfully elicit agent costs, complicated by the fact that it needs to balance multiple objectives. The main contributions of this work are: 1) multi-agent coordination on a network level through a novel combination of planning under uncertainty and dynamic mechanism design, applied to real-world problems, 2) accurate modelling and solving of maintenance-planning problems and 3) empirical exploration of the complexities that arise in these problems. We introduce a formal model of the problem domain, present experimental insights and identify open challenges for both the planning and scheduling as well as the mechanism design communities.